Statistical convergence in vector lattices - Aydın, A.; Temizsu, F. (Bulletin of the Karaganda University. Mathematics Series, 2023)
The statistical convergence is defined for sequences with the asymptotic density on the natural numbers, in general. In this paper, we introduce the statistical convergence in vector lattices by using the finite additive measures on directed sets. Moreover, we give some relations between the statistical convergence and the lattice properties such as the order convergence and lattice operators.